A survey of UK and Irish veterinary and veterinary nursing Students’ engagement with small animal nutrition information - Rachel H. Lumbis; Samantha J. Fontaine; John J. Reilly; Euan D. Bennet; Philippa S. Yam (PLoS ONE, 2026)
The global prevalence of diet-related non-communicable disease is rising, along with popularity of unconventional and alternative diets and the availability of unsubstantiated information. Considerable confusion and misinformation exist regarding nutrition and dietary choices. The veterinary healthcare team needs to be a trusted and primary source of sound nutritional advice and be able to signpost clients to appropriate nutrition information. This study’s objective was to establish the sources of nutrition information used by first-year veterinary students (VS) and veterinary nursing students (VNS) in the UK and Republic of Ireland. Participants were recruited by non-probability, convenience purposive sampling, by email invitation from educational providers. Data were collected between October 2023 and January 2024. Participation was voluntary and informed consent obtained. 135 VS and 186 VNS completed the online survey. Most (82%, n = 211) expressed an interest in learning about small animal nutrition. Qualified veterinarians were perceived to be more knowledgeable about pet nutrition (73%, n = 270) than veterinary nurses (53%, n = 132). Veterinary healthcare professional and journal articles ranked most valued sources of information, with media, social media, and friends/family least valuable. Students considered evidence-based information for dietary decisions by pet caregivers (93%, n = 213) to be important, yet only 53% (n = 138) felt sufficiently knowledgeable to access evidence-based nutritional information. This investigation highlights the paradox that trusted nutrition information sources are not always the most used. This insight into the nutrition information-seeking behaviour of student veterinary professionals can help inform educators in the provision of skills and knowledge to evaluate information and utilise trustworthy sources.